I-gel Laryngeal Mask Airway Combined with Tracheal Intubation Attenuate Systemic Stress Response in Patients Undergoing Posterior Fossa Surgery - Chaoliang Tang; Xiaoqing Chai; Fang Kang; Xiang Huang; Tao Hou; Fei Tang; Juan Li (Mediators of Inflammation)
Background. The adverse events induced by intubation and extubation may cause intracranial hemorrhage and increase of intracranial pressure, especially in posterior fossa surgery patients. In this study, we proposed that I-gel combined with tracheal intubation could reduce the stress response of posterior fossa surgery patients. Methods. Sixty-six posterior fossa surgery patients were randomly allocated to receive either tracheal tube intubation (Group TT) or I-gel facilitated endotracheal tube intubation (Group TI). Hemodynamic and respiratory variables, stress and inflammatory response, oxidative stress, anesthesia recovery parameters, and adverse events during emergence were compared. Results. Mean arterial pressure and heart rate were lower in Group TI during intubation and extubation (P<0.05 versus Group TT). Respiratory variables including peak airway pressure and end-tidal carbon dioxide tension were similar intraoperative, while plasma β-endorphin, cortisol, interleukin-6, tumor necrosis factor-alpha, malondialdehyde concentrations, and blood glucose were significantly lower in Group TI during emergence relative to Group TT. Postoperative bucking and serious hypertensions were seen in Group TT but not in Group TI. Conclusion. Utilization of I-gel combined with endotracheal tube in posterior fossa surgery patients is safe which can yield more stable hemodynamic profile during intubation and emergence and lower inflammatory and oxidative response, leading to uneventful recovery.